2015
DOI: 10.1542/peds.2014-3276
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding and Risk of Dental Malocclusion

Abstract: OBJECTIVES: The distinct effect of exclusive and predominant breastfeeding on primary dentition malocclusions is still unclear. We hypothesized that exclusive breastfeeding presents a higher protective effect against malocclusions than predominant breastfeeding and that the use of a pacifier modifies the association between breastfeeding and primary dentition malocclusions.METHODS: An oral health study nested in a birth cohort study was conducted at age 5 years (N = 1303). The type of breastfeeding was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 22 publications
(18 reference statements)
8
80
0
8
Order By: Relevance
“…in mixed dentition 8 , and the other eleven in primary dentition 4, 911, 1824 . The relationship between breastfeeding and overbite/anterior openbite was examined by fourteen studies, all in primary dentition 3, 6, 10, 12, 1821, 2429 . The relationship between breastfeeding and overjet/anterior crossbite in primary dentition was examined by six studies 3, 10, 18–20, 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in mixed dentition 8 , and the other eleven in primary dentition 4, 911, 1824 . The relationship between breastfeeding and overbite/anterior openbite was examined by fourteen studies, all in primary dentition 3, 6, 10, 12, 1821, 2429 . The relationship between breastfeeding and overjet/anterior crossbite in primary dentition was examined by six studies 3, 10, 18–20, 29 .…”
Section: Resultsmentioning
confidence: 99%
“…13, 14, 32, 33 investigated the same association in primary dentition. The relationship between breastfeeding and the development of occlusion/malocclusion was analyzed in nine studies, all in primary dentition 57, 1012, 18, 34, 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Corrêa-Faria et al 6 identified bottle feeding and deleterious oral habits as determinants for malocclusion in preschool children. Peres et al 7 , found that 34% of the children studied showed greater horizontal overjet, 37% showed anterior open bite, and 10% showed posterior crossbite in the deciduous dentition. These studies reinforce the importance of encouraging early abandonment of sucking habits as a preventive measure for the development of malocclusions.…”
Section: Discussionmentioning
confidence: 94%
“…However, Peres et al 7 found no association between maternal level of education and malocclusion. The association between the parents' level of education and the abandonment of the sucking habit was not significant in this study, considering that 39.9% of the children with the habit, who participated in the PPM, abandoned the habit in the first three months, regardless of their guardian's education level (Table 5).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation